NEUROBIOLOGY OF POST-TRAUMATIC STRESS DISORDER - Djorovic, Djordje (Medicinski podmladak, 2024)
Post-traumatic stress disorder (PTSD) is a psychiatric disorder which stems from exposure to severe trauma. It has a high comorbidity rate and increased mortality. This mini review is focused on presenting a concise state of the art overview of the neurobiology of PTSD. It starts with the explanation of the physiologic stress response followed by an elaboration of the function of specific systems in PTSD, including the autonomic nervous system, neuroendocrinology, inflammation, and neuroanatomy, and their role in the pathophysiology of PTSD. PTSD is prototype of disease influenced by gene environment interaction, thus every biological abnormality associated with PTSD can be vied either as a consequence or a risk factor for the emergence of the disease. The review is concluded by an elaboration of the contemporary therapeutic strategies for PTSD, including an overview of secondary prevention strategies which are currently investigated.